2013
DOI: 10.1097/ccm.0b013e318287f874
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cardiotonic Effects of Lipid Emulsion Infusion*

Abstract: Lipid emulsion exerts rapid, positive inotropic and positive lusitropic effects in both intact animal and isolated heart models. We hypothesize that this inotropy and the resulting increase in tissue blood flow contribute to the phenomenon of lipid reversal of cardiac toxicity caused by drug overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 52 publications
5
107
1
1
Order By: Relevance
“…Experimentally, rats infused with lipid emulsion showed an increased blood pressure and aortic flow rates relative to the same volume of saline. Additionally, isolated rat hearts in isovolumetric contraction were seen to contract more forcefully, with increased oxygen demand, when perfusate was augmented with lipid emulsion [11]. Stehr and colleagues [12] additionally demonstrated a positive effect on bupivacaine toxic cardiac myocytes at levels below those that could have effected any "sink" phenomenon.…”
Section: Cardiotonic Effectmentioning
confidence: 98%
“…Experimentally, rats infused with lipid emulsion showed an increased blood pressure and aortic flow rates relative to the same volume of saline. Additionally, isolated rat hearts in isovolumetric contraction were seen to contract more forcefully, with increased oxygen demand, when perfusate was augmented with lipid emulsion [11]. Stehr and colleagues [12] additionally demonstrated a positive effect on bupivacaine toxic cardiac myocytes at levels below those that could have effected any "sink" phenomenon.…”
Section: Cardiotonic Effectmentioning
confidence: 98%
“…Causing the inhibition of mitochondrial metabolism of lipids, ILE decreases tissue acidosis in myocardial ischemia and also decreases CO2 production [14]. It was also observed that ILE improved myocyte functions by increasing intracellular calcium level [16].…”
Section: Introductionmentioning
confidence: 96%
“…Providing energy resource to myocardium with a high dose of free fatty acid as another effect mechanism, it is considered that long chain fatty acids activate voltage -gated calcium channels in cardiac myocytes [13,14]. On the other hand, researches on ILE treatment continue anyway.…”
Section: Introductionmentioning
confidence: 99%
“…Several recently discovered applications and effects of lipid emulsions are described below. (17,18) by administering 20% soybean oil to male SpragueDawley rats and continuously measuring arterial pressure and aortic flow. Lipid infusion increased aortic flow and arterial pressure faster and to a greater extent than saline infusion.…”
Section: Introductionmentioning
confidence: 99%